2011
DOI: 10.1093/infdis/jir750
|View full text |Cite
|
Sign up to set email alerts
|

Hyporesponsiveness Following Booster Immunization With Bacterial Polysaccharides Is Caused by Apoptosis of Memory B Cells

Abstract: We demonstrated that the MenC-PS booster significantly reduced the frequency of newly activated MenC-PS-specific B cells-mostly switched IgG(+) memory cells-by driving them into apoptosis. It shows directly that apoptosis of PS-specific memory cells is the cause of PS-induced hyporesponsiveness. These results should be taken into account prior to consideration of the use of PS vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 32 publications
1
27
0
2
Order By: Relevance
“…We have shown in our neonatal murine model that meningococcal serogroup C polysaccharide (MenC-PS) also induces hyporesponsiveness in mice primed as neonates with a meningococcal C conjugate. The MenC-PS booster induced increased apoptosis of MenC-PS-specific B cells within 8–12 hours, mostly of switched IgG + memory cells [53]. Interestingly, the Pnc1-TT-induced PPS-1-specific long-lived plasma cells that had already homed to their survival niches in the BM were not affected by the PPS-1 booster s.c. and no significant difference was detected in their frequency 7 to 39 days after the booster.…”
Section: Discussionmentioning
confidence: 95%
“…We have shown in our neonatal murine model that meningococcal serogroup C polysaccharide (MenC-PS) also induces hyporesponsiveness in mice primed as neonates with a meningococcal C conjugate. The MenC-PS booster induced increased apoptosis of MenC-PS-specific B cells within 8–12 hours, mostly of switched IgG + memory cells [53]. Interestingly, the Pnc1-TT-induced PPS-1-specific long-lived plasma cells that had already homed to their survival niches in the BM were not affected by the PPS-1 booster s.c. and no significant difference was detected in their frequency 7 to 39 days after the booster.…”
Section: Discussionmentioning
confidence: 95%
“…It has been shown that a reduction in memory B-cells, and in particular B1b cells which are important in murine protection against pneumococcal disease, occurs in adults given PPS followed by PCV7, suggesting a mechanism for the limited effectiveness of PPS [35]. Studies in mice have revealed that such polysaccharide-induced hyporesponsiveness was associated with increased apoptosis of polysaccharide-specific B-cells when a booster immunization with a meningococcus serotype C polysaccharide vaccine was used [36]. Examination of the memory B-cell response in this Fijian cohort is currently underway and will provide important information as to the long term impact of this phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…Plain polysaccharide vaccines are thought to deplete the B MEM pool by inducing strong BCR cross-linking and driving the terminal differentiation of these cells into PCs, 25 or by inducing apoptosis as demonstrated in neonatal mice primed with MenCCV and boosted with MenCPS. 40 A recent study identified IgM-producing B cells as an important subset in the response to PPV-23 in young adults. 41 When the B cell response was compared between young and elderly adults, elderly participants had fewer IgM positive B cells and an impaired IgM response to vaccination.…”
Section: -Valent Pneumococcal Polysaccharide Vaccine (Ppv-23)mentioning
confidence: 99%